1988
DOI: 10.1016/s0022-5347(17)41709-5
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency and Side Effects of Prostaglandin El in the Treatment of Erectile Dysfunction

Abstract: The efficiency and side effects of a single dose of intracorporeally applied prostaglandin E1 (20 mcg.) in inducing penile erection were examined. In addition, the effect of this dose of prostaglandin E1 was compared to the effect of 7.5 mg. papaverine plus 0.25 mg. phentolamine in a double-blind, crossover designed study. We tested twice 12 men 52.9 +/- 7.6 years old (mean +/- standard deviation) with erectile dysfunction. On 1 occasion the subjects received 20 mcg. prostaglandin E1 and on the other they rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
1
1

Year Published

1989
1989
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(43 citation statements)
references
References 9 publications
2
39
1
1
Order By: Relevance
“…PGE1 10 ,ug still failed to induce erection in 15% of the subjects in the same group. In a previous report the authors showed that 20 ,ug PGE, is already within a therapeutic range, resulting in full erection in 11/12 patients suffering from erectile dysfunction of various causes (Waldhauser & Schramek, 1988). Thus the amount of PGE1 required as an initial test-dose for diagnostic differentiation between vasculogenic and nonvasculogenic impotence may lie close to 10 ,ug.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…PGE1 10 ,ug still failed to induce erection in 15% of the subjects in the same group. In a previous report the authors showed that 20 ,ug PGE, is already within a therapeutic range, resulting in full erection in 11/12 patients suffering from erectile dysfunction of various causes (Waldhauser & Schramek, 1988). Thus the amount of PGE1 required as an initial test-dose for diagnostic differentiation between vasculogenic and nonvasculogenic impotence may lie close to 10 ,ug.…”
Section: Discussionmentioning
confidence: 94%
“…(Roy et al, 1984), rapid elimination (Gruss et al, 1982) and probable metabolism in the corpora cavernosa (Hedlund & Andersson, 1985;Padma-Nathan et al 1987). Nevertheless, injection of PGE1 in a dose of 20 ,ug caused some discomfort to the patients (Waldhauser & Schramek, 1988 Finally a papaverine/phentolamine-test (test solution: 15 mg papaverine/0.5 mg phentolamine ml-') was performed in each patient (Stief et al, 1988). For this test 0.5 ml test solution was injected intracavernously.…”
Section: Introductionmentioning
confidence: 99%
“…Men who discontinued ICI did not differ from continuing ICI users on a number of demographic [2] 0.995; P b 0.40). To control for experimentwise error and possible correlations among covariates of ICI attrition, two multivariate logistic regressions were carried out on the signi®cant variables using attrition as the outcome variable.…”
Section: Comparison Of Ici Terminators and Continuersmentioning
confidence: 88%
“…812 The classical drugs (papaverine, papaverine plus phentolamine and prostaglandin El) for autoinjection therapy induce a full erec tile response in about 50 to 70% of an unselected population of men with erectile dysfunction. 13 " 21 The remaining patients with erectile dysfunction cannot be treated by autoinjection, al though they would fit into its selection criteria and be willing to accept this therapeutic option. Therefore, a new drug for intracavernous injection with a higher response rate is needed, at least for the latter patients.…”
Section: Abstract: Impotence Penile Erection Prostaglandins E Calmentioning
confidence: 99%